2017
DOI: 10.1021/acs.bioconjchem.7b00325
|View full text |Cite
|
Sign up to set email alerts
|

89Zr-Immuno-Positron Emission Tomography in Oncology: State-of-the-Art 89Zr Radiochemistry

Abstract: Immuno-positron emission tomography (immunoPET) with 89Zr-labeled antibodies has shown great potential in cancer imaging. It can provide important information about the pharmacokinetics and tumor-targeting properties of monoclonal antibodies and may help in anticipating on toxicity. Furthermore, it allows accurate dose planning for individualized radioimmunotherapy and may aid in patient selection and early-response monitoring for targeted therapies. The most commonly used chelator for 89Zr is desferrioxamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
159
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(168 citation statements)
references
References 68 publications
2
159
2
5
Order By: Relevance
“…The longer lived PET radionuclides 89 Zr and 124 I have been used to radiolabel intact antibodies, whilst the faster pharmacokinetics of antibody fragments have enabled the use of the shorter‐lived nuclides 18 F, 64 Cu, 44 Sc and 68 Ga for imaging. The fragment labelling strategy depends on both the particular isotope chosen and the available functionality on the particular fragment for conjugation.…”
Section: Labelling Strategies and Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The longer lived PET radionuclides 89 Zr and 124 I have been used to radiolabel intact antibodies, whilst the faster pharmacokinetics of antibody fragments have enabled the use of the shorter‐lived nuclides 18 F, 64 Cu, 44 Sc and 68 Ga for imaging. The fragment labelling strategy depends on both the particular isotope chosen and the available functionality on the particular fragment for conjugation.…”
Section: Labelling Strategies and Applicationsmentioning
confidence: 99%
“…Zirconium‐89 ( t 1/2 ≈78 h) is a longer lived PET radionuclide that has found applications for the labelling of intact antibodies and for larger antibody fragments such as minibodies and diabodies. The DFO ligand is commonly used to chelate 89 Zr IV , however, studies have demonstrated 89 Zr‐DFO complexes to be unstable in vivo, resulting in 89 Zr release and accumulation of 89 Zr in bone . Despite this, DFO has been mostly used for fragment labelling due to its high chelation yields, mild reaction conditions and reasonable stabilities.…”
Section: Labelling Strategies and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Readers interested in these efforts are directed to a comprehensive review by Heskamp et al 131 Though little clinical data is available on the metabolism of 89 Zr-labeled antibodies, it is interesting to note that the bone uptake patterns observed in mice are typically not seen in humans, leading many to believe that DFO is indeed a suitable chelator for 89 Zr in the clinic. 97,[132][133][134][135][136] Studies using 89 Zr-DFO-labeled trastuzumab in HER2-positive esophagogastric adenocarcinoma 136 and 89 Zr-labeled cmAb-U36 antibody in head and neck cancer 131 reported relatively low activity accumulation and retention in the liver and spleen. In contrast, higher activity concentrations were observed in both organs during trials with 89 Zr-huJ591, 97 89 Zrcetuximab, 133 and 89 Zr-rituximab.…”
Section: Zirconium-89mentioning
confidence: 99%